Benzimidazole and its derivatives as cancer therapeutics: The potential role from traditional to precision medicine - Yeuan Ting Lee; Yi Jer Tan; Chern Ein Oon (Elsevier, 2023)
Cancer is the second leading cause of mortality globally which remains a continuing threat to human health today. Drug insensitivity and resistance are critical hurdles in cancer treatment; therefore, the development of new entities targeting malignant cells is considered a high priority. Targeted therapy is the cornerstone of precision medicine. The synthesis of benzimidazole has garnered the attention of medicinal chemists and biologists due to its remarkable medicinal and pharmacological properties. Benzimidazole has a heterocyclic pharmacophore, which is an essential scaffold in drug and pharmaceutical development. Multiple studies have demonstrated the bioactivities of benzimidazole and its derivatives as potential anticancer therapeutics, either through targeting specific molecules or non-gene-specific strategies. This review provides an update on the mechanism of actions of various benzimidazole derivatives and the structure‒activity relationship from conventional anticancer to precision healthcare and from bench to clinics.